A STUDY OF POP-UP SPACE TO DETERMINE UTILITIES SPACE FOR FASHION POP-UP STORE - Gleblumjeak, Sahapop; Suteeweerakajorn, Worawut (Fine Arts Journal: Srinakharinwirot University, 2020)
This study aims to develop a guideline for designing a practical layout of a pop-up store that can be adjusted to suit the limited space but still maintains the proper utilities of a fashion store. The study is divided into two main aspects which are (1) the analysis of area selection based on the perspectives of shop owners and (2) the analysis of space for displaying products. In term of the area selection, the most popular venues are an event-space followed by an in-line shopping center stores. The specifications for these areas are as follows: (1) the proper space dimension for a pop-up store should be about 4 square meters with the height not more than 2 meters, and the space should be expanded by 1 meter apiece according to the increasing space. (2) In term of the space for displaying products, (i) the hanging areas for clothes should be located in the front and on both sides of the pop-up store with two different widths (i.e. 0.25 meters and 0.5 meters), three different heights (i.e. 0.7 meters, 1.0 meters, and 1.8 meters), and not over 0.5 meters in depth, (ii) the area for displaying folded clothes should be 0.25-0.45 meter shelves depending on the items and folding techniques (the minimum height is 2.5 meters with not less than 0.45 meters in depth), and (iii) the shoe display space should be at least 0.12 x 0.3 meters for one piece of shoes with 0.25 meters minimum in height of the space between each level of the shelve.